2018
DOI: 10.1007/s00345-018-2319-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprophylaxis during transrectal prostate needle biopsy: critical analysis through randomized clinical trial

Abstract: Augmented prophylaxis with single-dose gentamicin is an effective and practical approach. Targeted prophylaxis might be reserved for cases with contraindication to gentamicin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…35e40 However, the largest RCT used only a single shot targeted prophylaxis compared to a 3-day regimen of standard or augmented prophylaxis and showed comparable infectious complications with targeted and empiric prophylaxis. 35 This is in concordance with our analysis showing that a single shot prophylaxis is insufficient.…”
Section: Discussionsupporting
confidence: 91%
“…35e40 However, the largest RCT used only a single shot targeted prophylaxis compared to a 3-day regimen of standard or augmented prophylaxis and showed comparable infectious complications with targeted and empiric prophylaxis. 35 This is in concordance with our analysis showing that a single shot prophylaxis is insufficient.…”
Section: Discussionsupporting
confidence: 91%
“…Elshal et al compared the post-transrectal biopsy infectious complication (TBIC) rate between patients separated into standard (3 days 500mg ciprofloxacin twice daily, beginning the night before the biopsy), augmented (ciprofloxacin and single 160mg gentamicin IM), and targeted prophylaxis (based on results of rectal swab cultures). There was a lower rate of TBICs among the patients allocated to the augmented prophylaxis group, regardless of the variation in the number of biopsy cores taken when compared to the other two groups [10].…”
Section: Prophylaxis Of Uti Following Transrectal Biopsymentioning
confidence: 80%
“…While in two studies infectious complications occurred only in the standard prophylaxis group [20,21], the third study showed an equal distribution of infectious complications [19]. Of note, the later study demonstrated an unusually high rate of infectious complications with a sepsis rate of 5.2% among all groups [19]. To give a final recommendation, a meta-analysis of the available RCTs is mandatory.…”
Section: Targeted Antibiotic Prophylaxismentioning
confidence: 99%
“…The authors further concluded that fluoroquinolone resistance drives the higher rates of infectious complications in the standard antibiotic prophylaxis group [18]. To date, a total of three RCTs have been published involving 1337 patients [19][20][21] (Table 2).…”
Section: Targeted Antibiotic Prophylaxismentioning
confidence: 99%